Visualisation of Animals by Children: How Do They See Birds? - Sue Dale Tunnicliffe (Center for Educational Policy Studies Journal)
Children learn to recognise animals from their earliest years through actual sightings in their own observations of their world, but also through second-hand representations in various forms of media. Young learners begin with a template specimen to which they refer when they see another animal that resembles it, naming the animal accordingly. Gradually, they learn to distinguish members of the subordinate category – bird in the case of the present paper – into subcategories. Accessing their mental model through drawings is one means of discerning their interpretation of both phyla and species. If children of increasing ages are studied, a rationale for the understanding of a such concepts may be forthcoming. The present study investigated children from 6 years to 14 years though interviews, as well as through the drawings on which the paper focuses. As children mature, they observe more and more details about the birds that they see, thus increasing their knowledge not from school but from their own observations outside school.